MODELS OF QUALITATIVE ESTIMATION OF AIR TRAFFIC FLOWS AND CAPACITY IN TERMINAL CONTROL AREAS - Kharchenko, Volodymyr; Chynchenko, Yuriy (Proceedings of National Aviation University (archive), 2016)
Purpose: The aim of this study is to research applied models of qualitative estimation of air traffic flow and capacity in terminal control area (TMA) under uncertainty conditions. In this work the theoretical framework descripting departing and arriving air traffic flows in order to regulate capacity and decrease delays in terminal control areas airspace is proposed. Methods: Optimisation of terminal control area formal description based on composite model of typical airspace elements and operational procedures, reduction of delays on runways and in the airspace in vicinity of aerodrome using the airport and terminal control area operations optimisation model, assessment of various types of uncertainties and associated factors by application of terminal control area queueing analysis uncertainty model. Results: Terminal control area descriptive model, airport and TMA operations optimisation model and TMA queueing analysis uncertainty model were obtained. Principles of estimating of quantitative parameters of air traffic flows and capacity in terminal control areas under uncertainty conditions were proposed. Discussion: Composite elements of terminal control area descriptive model, principles of delays reduction as a result of application of airport and TMA operations optimisation model and assessment of impact of uncertainty factors in air traffic control and flight operations by TMA queueing analysis uncertainty model.